To Succeed or Perish : The Diaries of Sergeant Edmund Trent Eggleston, Company G, 1st Mississippi Light Artillery Regiment, CSA - Eggleston, Edmund Trent, 1833-1896 (Book collections on Project MUSE., 2015)
"With the Conscription Act of 1862, the Confederacy enacted the first military draft in American history. Rather than face duty with strangers in an uncertain locale, twenty-eight-year-old Edmund Trent Eggleston of Warren County, Mississippi, took advantage of a thirty-day grace period and joined his neighbors in volunteering for duty in Company G of the 1st Mississippi Light Artillery Regiment. Throughout his service, Eggleston kept a detailed account of his daily activities and those of his unit, a diary that remains one of the very few primary sources from a Confederate artillerist in the West. In To Succeed or Perish, editors Lawrence Lee Hewitt, Thomas E. Schott, and Marc Kunis present Eggleston's diaries, along with his letters and ledgers, to offer a rare personal perspective on life behind the cannon in the Civil War's Western Theater and a fascinating window into the world of the Confederate soldier. Eggleston describes garrison duty near Vicksburg, where he enjoyed visits from his wife and children; the battery's first engagement with the enemy at Champion Hill on May 16, 1863; and his service during the 1864 campaigns in Georgia and Tennessee. He offers a significant firsthand account of the Atlanta campaign, including the fightings at Resaca, Cassville, New Hope Church, Kennesaw Mountain, and the Chattahoochee River, as well as the siege of Atlanta. Because of the destruction of Hood's Army, Confederate records of these engagements are extremely rare, and Eggleston's observations are invaluable. In Tennessee, he recounts the action at the Battle of Nashville and the capture of his battery. Featuring an introduction that traces the wartime actions of Company G as well as a complete roster of the men with whom Eggleston served, To Succeed or Perish provides an important primary account of artillery service in an underrepresented theater of the Civil War"--